The Continued Mistreatment of Women During Pregnancy and Childbirth (J Perinat Educ, 2019)
Mistreatment of women during pregnancy and childbirth continues to define our American way of birth in spite of decades of awareness and concern. The Giving Voice to Mothers study identifies the incidence of mistreatment of childbearing women in the United States, the factors that increase a woman's risk of being mistreated including socio economic and racial characteristics, place of birth, and health-care provider. This editorial highlights the study findings, the role of the current maternity care system in perpetuating inequality and mistreatment, and calls on all stakeholders to create a culture that cares for women with respect and dignity. The editor also describes the contents of this issue, which offer a broad range of resources, research, and inspiration for childbirth educators in their efforts to promote, support, and protect natural, safe, and healthy birth.